Blood Lead Levels in Mexico and Pediatric Burden of Disease Implications - Jack Caravanos; Russell Dowling; Martha María Téllez-Rojo Dra; Alejandra Cantoral; Roni Kobrosly; Daniel Estrada; Manuela Orjuela; Sandra Gualtero; Bret Ericson MSc; Anthony Rivera; Richard Fuller (Ubiquity Press, 2014)
Background: Although there has been success in reducing lead exposure with the phase-out of leaded gasoline, exposure to lead in Mexico continues to threaten the health of millions, much of which is from lead-based glazes used in pottery that leaches into food. Objectives: An extensive historical review and analysis of available data on blood lead levels in Mexican populations was conducted. We used a calculated geometric mean to evaluate the effect of lead on the pediatric burden of disease. Methods: An extensive bibliographic search identified 83 published articles from 1978 to 2010 with blood lead level (BLL) data in Mexican populations representing 150 data points from more than 50,000 study participants. Values from these publications were categorized into various groupings. We then calculated the incidence of disease and disability-adjusted life-years resulting from these BLLs using the World Health Organization's burden of disease spreadsheets for mild mental retardation. Results: Reviewing all relevant studies, the geometric means of Mexican BLLs in urban and rural areas were found to be 8.85 and 22.24 ug/dL, respectively. Since the phase-out of leaded gasoline, the mean in urban areas was found to be 5.36 ug/dL and the average in rural areas is expected to be much higher. The U.S. Centers for Disease Control and Prevention's (CDC) upper limit of blood lead in children under the age of 6 years is 5 ug/dL and the current U.S. average is 1.2 ug/dL. Our results indicate that more than 15% of the population will experience a decrement of more than 5 IQ points from lead exposure. The analysis also leads us to believe that lead is responsible for 820,000 disability-adjusted life-years for lead-induced mild mental retardation for children aged 0 to 4 years. Conclusion: Lead continues to threaten the health of millions and remains a significant cause of disability in Mexico. Additional interventions in reducing or managing lead-based ceramic glazes are necessary to protect the public health.